Influence of harvesting and processing methods on organic viability of soybean seed - Đukanović Lana; Srebrić Mirjana; Milićević Miloš; Pavlov Milovan (Selekcija i Semenarstvo, 2000)
Organic viability of soybean seed for three soybean varieties - elite (Bosa, ZPS 015 and Nena) depending on methods of manipulation with seeds during harvesting and processing phase were determined in this paper. Trial was conducted in Zemun Polje during 1999; manual and mechanized harvesting or processing methods were applied. Seed germination was tested using ISTA methods (Standard method and Cold test). Following parameters were evaluated: germination viability, germination, rate-speed of emergence, length of hypocotile and main root Rate-speed of emergence was based on number of emerged plants per day. Length of hypocotile or root and percent of germination determined vigour index. Based on obtained results it maybe concluded that methods of seed manipulation during harvesting or processing phase were influenced on soybean seed quality parameters evaluated. Ways of seed manipulation - methods evaluated were influenced organic viability of soybean seed by decreasing germination viability, total germination and length of main root.